Quality of Brosimum gaudichaudii seedlings and seeds collected in two different locations - Ribeiro, Alcy Flávia Silva; Silva, Givanildo Zildo da; Machado, Carla Gomes; Dias, Daniela Pereira (Scientia Agraria Paranaensis, 2022)
The seed provenance can interfere with their size, as well as in the growth of saplings and susceptibility to stress. The aim of this study was to evaluate the quality of Brosimum gaudichaudii Trécul seeds and seedlings obtained from two different locations. Seeds were collected in two municipalities in the state of Goiás - Iporá and Jataí, in 2018. Individual seed size mass and dimension, seedling emergence percentage and speed, as well as initial growth, leaf chlorophyll index, biomass and seedling quality index (SQI) were determined. Such parameters were determined at 40, 70, 100, 130, 160 and 190 days after sowing (DAS). Individual size mass and dimension of seed collected in Iporá were superior to those collected in Jataí. Despite this, the seedling emergence percentage and seedling mortality were not affected by the different origins of seeds. As expected, there was increase in height, stem diameter and number of leaves of seedlings during the analyzed period, on the other hand, the chlorophyll index remained constant. The initial growth of seedlings differed between origins. The dry biomass did not vary between seedlings from the different origins, with greater allocation of biomass in roots. The SQI of seedlings produced from seeds collected in Iporá was higher than those collected in Jataí. Despite the quality verified for seeds and seedlings from the two origins, seeds collected in Iporá presented larger dimensions than those collected in Jataí, generating seedlings with greater initial growth and higher quality.